Nitrogen and carbohydrate fractions in exclusive Tifton 85 and in pasture oversown with annual winter forage species - 10.4025/actascianimsci.v34i1.11428 - Andréia Luciane Moreira; Ricardo Andrade Reis; Flávia Fernanda Simili; Carlos Augusto de Miranda Gomide; Ana Claudia Ruggieri; Telma Terezinha Berchielli (Acta Scientiarum. Animal Sciences, 2011)
The experiment was undertaken at the Faculty of Agrarian and Veterinary Sciences (FCAV) Jaboticabal, São Paulo State, Brazil, during winter-spring-summer of 2001-2002, to determine the fractionation of nitrogen and carbohydrates in Tifton 85 (Cynodon dactylon Vanderyst x Cynodon nlemfuensis (L.) Pers), exclusively or oversown with winter annual forage species. Treatments comprised bristle oat (Avena strigosa Schreb), yellow oat (Avena byzantina C. Koch), triticale (X Triticosecale Wittmack), bristle oat + yellow oat, bristle oat + triticale, yellow oat + triticale, bristle oat + yellow oat + triticale seeded in Tifton 85 and sole crop (control). Experimental design was composed of completely randomized blocks with three replications. Fodder was cut 20 cm high (presence of winter forage) and 10 cm high (Tifton 85 pasture). Crude protein, total carbohydrate and the fractions of nitrogen compounds and carbohydrates were determined. Decrease was reported in the levels of chemical compounds in winter forage species and in Tifton 85 during the evaluation periods. The content of nitrogen compounds and carbohydrates varied widely during the evaluation period according to the morphological characteristics of grass species and botanical composition of pastures.